2012
DOI: 10.4103/1119-3077.97317
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of cutaneous drug reactions in a private dental college and government medical college in eastern India

Abstract: Commonest drugs causing drug reactions are antibiotics mainly beta lactams and quinolones. Severe reactions were seen in our series with anticonvulsants and NSAIDS. Association with other diseases could not be inferred due to this modest patient pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 3 publications
3
16
0
Order By: Relevance
“…Altogether we observed 18 different types of cutaneous adverse drug reactions. Exanthematous type was the commonest type of reaction observed in our study which is in accordance to the finding of several other authors 4,8,12,[15][16][17] . Fixed drug eruption was the second most common drug eruption seen in our study similar to the finding of Patel RM et al 18 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Altogether we observed 18 different types of cutaneous adverse drug reactions. Exanthematous type was the commonest type of reaction observed in our study which is in accordance to the finding of several other authors 4,8,12,[15][16][17] . Fixed drug eruption was the second most common drug eruption seen in our study similar to the finding of Patel RM et al 18 .…”
Section: Discussionsupporting
confidence: 93%
“…Antimicrobials was the commonest drug category of drug involved in CADR observed by several authors 8,12,16 . Antibiotic was the most common cause of CADR in our study.…”
Section: Discussionmentioning
confidence: 97%
“…Of the various cutaneous ADRs, Fixed Drug Eruption including the bullous variant was the commonest, seen in 64 (45.71%) patients, similar to the findings of study by Chatterjee et al, 2 Patel et al, 3 Qayoom et al, 4 but in contrast to Chattopadhyay et al, 5 Jha et al, 6 Saha et al, 7 Hiware et al 8 and Jhaj et al 9 Maculopapular Rash followed this in 24(17.14%), followed by SJS in 16 (11.42%). Fifteen cases of FDE and three cases of its bullous variant were caused by Fixed dose combination of ofloxacin and ornidazole.bMale preponderance was seen with a M: F ratio of 2.25: 1.This was similar to the findings by Sharma et al 10 and Patel et al 3 However studies by Chattopadhyay et al, 5 Nandha et al, 11 Sehgal et al 12 and Pudukadan et al 13 showed an equal or a female preponderance. Higher male proportion in our study could be because of medical seeking behavior of males.…”
Section: Discussionsupporting
confidence: 85%
“…11,12,15 This may be due to different prescription pattern by physicians or selfmedication in various setting for pain and fever. 11,12,[15][16][17]19,20 Anti-retroviral drugs and anti-convulsants are the common drugs causing severe drug reactions (11,6.5%) as SJS, TEN and DHS, amongst which SJS (6, 3%) was the commonest and these results were comparable to studies by Chatterjee et al and Chattopadhyay et al 3,7 The definite diagnosis was done in 28 cases (14%), possible in 56 cases (28%) and probable in 116 cases (58%) almost similar to study done by Puavilai et al and was in contrast to Thong et al study but the drawback of this assessment is the possibility of personal bias can be present because of disagreement in the causality assessment. 21,22 Limitations of our study were the definite association of drug reaction was not done in all patients as consent was not given in few cases and it was not done in severe drug reactions.…”
Section: Discussionsupporting
confidence: 60%
“…6 The current classification of adverse drug reactions (Table 4) which is most accepted is: a) Nonimmunological, b) Immunological (unpredictable) and c) miscellaneous. 6 Immunologic reactions require host immunological pathway, activation of host whereas nonimmunologic mechanisms occur due to side effects, overdosage, exacerbation of pre-existing conditions, etc 7 . Almost 75-80% of adverse drug reactions are caused by predictable, non-immunologic effects, remaining 20-25% are caused by unpredictable effect suggesting that majority was predictable.…”
Section: Discussionmentioning
confidence: 99%